1991
DOI: 10.1007/bf00221343
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of pertussis infection in an urban childhood population in Cameroon

Abstract: In 1989, the prevalence of IgG antibodies to pertussis toxin (PT) in a sample of 367 unvaccinated apparently healthy children 5-14 years old was estimated by ELISA in Kumba City (Cameroon). Children were recruited using a systematic random sampling from six primary schools located in different districts of the city. The sample was representative of the various socioeconomic classes. The overall prevalence was 75%; it increased from 62% in 5 year old children to 81% in children 12-14 years old (P less than 0.01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Although household size has been found to have no influence on the rate of infection [23, 24], Strofolini et al . concluded that for children from a household of ⩾9 members, aPT antibody values were 2·2 times higher than those with <9 members [25].…”
Section: Discussionmentioning
confidence: 99%
“…Although household size has been found to have no influence on the rate of infection [23, 24], Strofolini et al . concluded that for children from a household of ⩾9 members, aPT antibody values were 2·2 times higher than those with <9 members [25].…”
Section: Discussionmentioning
confidence: 99%
“…There were five studies which reported epidemiology data for pertussis in Africa, namely Senegal [ 27 ], Tunisia [ 28 ], Algeria [ 29 ], Nigeria [ 30 ], and Uganda [ 31 ], and seven studies which reported sero-epidemiology in Senegal [ 32 ], Cameroon [ 33 ], South Africa [ 34 ], Tunisia [ 35 , 36 ], Morocco [ 37 , 38 ], and Gambia [ 39 ]. There were seven studies with mortality data including Nigeria [ 30 , 40 ], Ethiopia [ 41 ], Morocco [ 42 ], South Africa [ 43 , 44 ], and Senegal [ 27 ].…”
Section: Search Resultsmentioning
confidence: 99%
“…Anti-PT IgG levels were assessed in 365 children, and overall, 75% were seropositive (PT IgG levels three times the mean value of negative sera [PT IgG < 80 IU/ml] obtained from young children). Seroprevalence increased significantly by age: 5 years, 62%; 6–7 years, 67%; 8–9 years, 73%; 10–11 years, 82%; and 12–14 years, 81% ( p < 0.001) [ 33 ].…”
Section: Search Resultsmentioning
confidence: 99%
“…Whole-cell sonicates (WC) of B. pertussis were used as antigens for ELISAs in the 1980s [3,[12][13][14] but were gradually replaced by purified antigens: pertussis toxin (PT), filamentous haemagglutinin (FHA), pertactin (PTN) and fimbrial proteins (FIM). PT and FHA ELISAs were utilized in serosurveys to assess population immunity and exposure to B. pertussis [15][16][17][18][19] and the presence of PT antibodies has been correlated with protection against pertussis [20][21][22]. Assays for IgG, IgM and IgA to PT and FHA have been used extensively during vaccine trials in which they were thoroughly validated [23][24][25][26][27] and showed high specificity for the detection of recent infections by B. pertussis [28,29].…”
Section: Introductionmentioning
confidence: 99%